Mineral Commodity Summaries 1986 - An Up-To-Date Summary Of 87 Nonfuel Mineral Commodities - Significant Events In The Nonfuel Mineral Industry In 1985 (The National Institute for Occupational Safety and Health (NIOSH), 1986)
The value of domestic raw nonfuel mineral output in 1985 was estimated at $23.7 billion, 2% above the 1984 value of $23.1 billion. This crude mineral output was the basis for approximately $244 billion worth of processed materials of mineral origin. [ ] A U.S. company permanently closed its alumina plant in St. Croix, U.S. Virgin Islands, reducing domestic alumina capacity by 10%. Another U.S. company sold its 26% interest in an alumina plant in Jamaica to its two U.S. partners. On completion of the purchase agreement, the two remaining partners promptly closed the plant for an indefinite period, citing a world oversupply of alumina and unacceptably low prices.